2015
DOI: 10.3944/aott.2015.14.0135
|View full text |Cite
|
Sign up to set email alerts
|

A detailed analysis of messages posted on the ‘Turk-Orthopod’ mailing list over a 13-year period

Abstract: The 'Turk-Orthopod' mailing list serves primarily as an information board and a powerful social media platform for communication among Turkish orthopedic surgeons. However, scientific case discussions and other professional issues comprise a minority of the messages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…17 There have been similar reports on the success of existing listservers by some other groups, [18][19][20] although some others reported that although they functioned well as information boards, they did not function effectively for scientific case discussions. 21,22 Given the mixed experience with the use of email listservers, our focus was to specifically assess the use of mobile phone applications in facilitating online clinical discussions. There are a number of online medical communities on publicly accessible websites and also on different platforms including, but not limited to, Facebook, Googleþ and Twitter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 There have been similar reports on the success of existing listservers by some other groups, [18][19][20] although some others reported that although they functioned well as information boards, they did not function effectively for scientific case discussions. 21,22 Given the mixed experience with the use of email listservers, our focus was to specifically assess the use of mobile phone applications in facilitating online clinical discussions. There are a number of online medical communities on publicly accessible websites and also on different platforms including, but not limited to, Facebook, Googleþ and Twitter.…”
Section: Discussionmentioning
confidence: 99%
“…17 There have been similar reports on the success of existing listservers by some other groups, 1820 although some others reported that although they functioned well as information boards, they did not function effectively for scientific case discussions. 21,22…”
Section: Discussionmentioning
confidence: 99%
“…Review of literature reveal many studies conducted on the mailing groups used by different professionals to achieve their professional objectives such as for Social work (Matzat, 2009), for music (Mitchell, 1997), for health (Köse et al, 2015; Hernández-Borges et al, 1998, 1999; McLauchlan et al, 1999; Morken et al, 2009; Serrano-Castro et al, 2004), for Pharmacists (Whitaker et al, 2003), and by teachers (Bodell and Hook, 2014; Brouns et al, 2011; Fernández-Pérez et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…CoPs have been widely adopted by different professionals, i.e. by health professionals (Hern andez-Borges et al, 1998;Hernandez-Borges et al, 1999;K€ ose et al, 2015;Morken et al, 2009), by pharmacists (Whitaker et al, 2003), by social workers (Matzat, 2009), by musicians (Mitchell, 1997), by academicians (Bodell and Hook, 2014;Brouns et al, 2011;Fern andez-P erez et al, 2015), and by librarians (Choi et al, 2019) for knowledge sharing and continuous professional development (CPD). The studies in this field examined the evolution of VCoP.…”
Section: Introductionmentioning
confidence: 99%